Distribution of Bacterial α1,3-Galactosyltransferase Genes in the Human Gut Microbiome - Montassier, Emmanuel; Al-Ghalith, Gabriel A.; Mathé, Camille; Le Bastard, Quentin; Douillard, Venceslas; Garnier, Abel; Guimon, Rémi; Raimondeau, Bastien; Touchefeu, Yann; Duchalais, Emilie; Vince, Nicolas; Limou, Sophie; et al. (Frontiers in Immunology, 2020)
Because of a loss-of-function mutation in the GGTA1 gene, humans are unable to synthetize α1,3-Galactose (Gal) decorated glycans and develop high levels of circulating anti-α1,3-Galactose antibodies (anti-Gal Abs). Anti-Gal Abs have been identified as a major obstacle of organ xenotransplantation responsible for hyperacute vascular rejection and delayed vascular insult, and play a role in several host-pathogen relationships including potential susceptibility to infection. Anti-Gal Abs are supposed to stem from immunization against the gut microbiota, an assumption derived from the observation that some pathogens display α1,3-Gal and that antibiotic treatment decreases the level of anti-Gal. However, there is little information to date concerning the microorganisms producing α1,3-Gal in the human gut microbiome. Here, available α1,3-Galactosyltransferase gene sequences from gut bacteria were selectively quantified for the first time in the gut microbiome shotgun sequences of 163 adult individuals from 2 published population-based metagenomics analyses. We showed that most of the gut microbiome of adult individuals contained a small set of bacteria able to synthetize the α1,3-Gal antigen. The Enterobacteriaceae family, including Escherichia coli, was found to be the major source of the α1,3-Gal antigen, which was also produced by Pasteurellaceae genera, Haemophilus influenza, and Lactobacillus species.